Preparation, characterization, and morphology of on/off detection indicator based on rhodamine 6G‐adamantanamine loaded onto nonwoven polyethylene terephthalate. Issue 9 (12th May 2020) - Sun, Wuliang; Fan, Liyan; Zhao, Yujia; Dong, Tungalag; Jin, Ye; Saldaña, Marleny D.A.; Sun, Wenxiu
Abstract : Traditionally, food quality is evaluated by consumers through comparison of the production and expiration dates of the product. However, product shelf life cannot be the real and only parameter of food quality, especially within a variety of storage environments. Therefore, new indicators of food quality are needed to provide food safety to the consumer. In this work, we reported a detection indicator based on rhodamine 6G‐adamantanamine and β‐cyclodextrin (β‐CD) polyelectrolyte cross‐linked onto a nonwoven polyethylene terephthalate textile support, which can be used as the indication of food quality by means of the irreversible change of fluorescence. The relationship between the increase of fluorescence and pH variation was also reported. Considering food safety, a migration experiment was carried out using a food simulation system. When pH changed to 6.8, the evident fluorescence can be observed by naked eye at 650‐nm excitation wavelength. β‐CD can not only act as a good carrier of rhodamine 6G‐adamantanamine but also enhanced the fluorescence to indicate whether rhodamine 6G‐adamantanamine was loaded onto β‐CD polyelectrolyte or nonwoven polyethylene terephthalate. After 250 h of migration experiment at 25°C, it was found that the fluorescent substances slightly migrated, and the migration under acidic conditions was almost negligible. The fluorescence enhancement performance and migratory behavior indicated that the material had the potential as a fluorescent intelligent indicator for food packaging. Abstract : Traditionally, food quality is evaluated by consumers through comparison of the production and expiration dates. However, product shelf life cannot be the real and only parameter of food quality. Therefore, new indicators of food quality are needed to provide food safety to the consumer. In this work, we reported a detection indicator based on rhodamine 6G‐adamantanamine loaded onto nonwoven polyethylene terephthalate, which can be used as the indication of food quality by means of the irreversible change of fluorescence.